Improving cardiovascular health in black men through a 24-week community-based team lifestyle change intervention: The black impact pilot study - Joshua J. Joseph; Timiya S. Nolan; Amaris Williams; Alicia McKoy; Songzhu Zhao; Emmanuela Aboagye-Mensah; Bjorn Kluwe; James B. Odei; Guy Brock; Dana Lavender; John Gregory; Darrell M. Gray, II (Elsevier, 2022)
Background: Higher cardiovascular health scores, using American Heart Association's (AHA) Life's Simple 7 (LS7), have been associated with lower risk of cardiovascular disease, type 2 diabetes, cancer, and mortality among all racial/ethnic groups. Nationally, Black men have the lowest levels of LS7. Thus, a study was conducted to evaluate the impact of a community-based team lifestyle change program on LS7 among Black men. Methods: Black adult males (n = 74) from a large Midwestern city participated in Black Impact, a 24-week community-based team lifestyle change program adapted from the Diabetes Prevention Program and AHA's Check, Change, Control Blood Pressure Self-Management Program, which incorporates AHA's LS7 framework. The change in a LS7 score (range 0-14) from baseline to 12 and 24 weeks was evaluated using a linear mixed-effects model adjusted for age, education, and income. Results: The mean age of participants was 52 ± 10 years. The men were sociodemographically diverse, with annual income ranging from <$20,000 (7%) to ≥$75,000 (25%). Twenty-five percent were college graduates, 73% had private insurance, and 84% were employed. In fully adjusted models, LS7 score at baseline was 7.12 and increased 0.67 (95%CI: 0.14, 1.20, p = 0.013) and 0.93 (95%CI: 0.40, 1.46, p<0.001) points at 12 and 24 weeks, respectively, compared to baseline. Sensitivity analysis evaluating 5 components (excluding diet and physical activity) and 6 components (excluding diet) also showed significant increases at 12 and 24 weeks (all p<0.01). Conclusions: The Black Impact lifestyle change single-arm pilot program showed that a community-based lifestyle intervention has the potential to improve LS7 in Black men. Further randomized studies are urgently needed to improve cardiovascular health and advance cardiovascular health equity in Black men.